Singapore and the "power of free". - Hana Suri. (2009)
The Power of Free is a relatively new phenomenon that has been proposed by Dan Ariely and others. This paper attempts to test this phenomenon in Singapore, using SMRT’s Early Bird Travel Perks promotion with additional twists. It is argued that the Power of Free would be very prominent due to the kiasu nature of Singaporeans. It is predicted to yield a finding greater than the 70-percent irrationality found by Ariely. Data was collected in the form of 48 interviews (37 working adults and 11 tertiary students) and 1,595 surveys completed by students. A probit model regression was run and the data results explained. A 46-percent incidence of irrationality for the interviews and 60-percent irrationality for the surveys were calculated. The results showed that for the interviews sleep foregone, importance of sleep, comfort level on the trains and being late were significant factors in determining whether an individual will select a free good. However, both the interview and survey show that WTA had a low influence on the decision of accepting a free breakfast. An anomaly in the findings of the survey is the negligible impact of comfort level on choosing a free breakfast. The large constant terms for both interviews and surveys hinted at omitted variable bias and this was explained with the use of factors such as loss aversion, transaction utility, endowment effects and the classification of sleep either as a luxury or necessity. Limitations of the experiment are also discussed.